1972
DOI: 10.1103/physrevlett.29.1233
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Cyclotron Resonance in Surface-Bound Electrons on Liquid Helium

Abstract: We have observed cyclotron resonance from electrons in two-dimensional states outside liquid helium. Their resonant frequency depends only on the perpendicular component of the applied magnetic field, and their observed mobility is that expected for electrons scattered parallel to the liquid surface in only two dimensions, In a recent Letter, Ostermeier and Schwarz 1 have presented data questioning the existence of image-potential-induced surface states for electrons outside of liquid helium. These states had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(38 citation statements)
references
References 8 publications
2
36
0
Order By: Relevance
“…1.3 K and low input powers. We pay additional attention to the power dependence of the experimental data, since we found that, at lower powers, the weak power broadening of the linewidth also observed in [3] turns into power narrowing and the extrapolation to zero power input cannot be used.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…1.3 K and low input powers. We pay additional attention to the power dependence of the experimental data, since we found that, at lower powers, the weak power broadening of the linewidth also observed in [3] turns into power narrowing and the extrapolation to zero power input cannot be used.…”
mentioning
confidence: 96%
“…+ b Cyclotron resonance (CR) studies in two-dimensional (2D) electron systems such as inversion layers on semiconductor surfaces and electrons bound at the free surface of liquid helium have been of great interest for many years [1,2]. Cyclotron resonance serves as a powerful probe for the effects of quantization of both out-of-plane and in-plane (orbital) motions on electron transport phenomena [3,4]. Two-dimensional electrons on a liquid helium surface are usually under extremely strong coupling conditions with respect to mutual Coulomb interaction: e 2 p pn s ͞k B T ¿ 1 (here n s is the electron density).…”
mentioning
confidence: 99%
“…This phenomena has been observed [6]- [8]. (See [9] for a current review and [10] for a proposed application to quantum computing.…”
mentioning
confidence: 99%
“…When the two-dimensional gas is inserted into a transverse magnetic field H the energy spectrum of the carriers (for the sake of concreteness we shall consider electrons) is transformed into a set of discrete Landau levels. Optical absorption due to the transitions of electrons between these levels (cyclotron resonance) was observed in the liquid He-gaseous He interface [3] and in the inversion layer of p-type Si [4 to 61.…”
Section: Introductionmentioning
confidence: 99%